2008
DOI: 10.1126/science.1159174
|View full text |Cite
|
Sign up to set email alerts
|

Comment on "Determining Chondritic Impactor Size from the Marine Osmium Isotope Record"

Abstract: Paquay et al . (Reports, 11 April 2008, p. 214) reported that osmium isotope ratios in marine sediments can be used to determine the size of a chondritic impactor. Their assumptions on the fate of an impacting projectile may need to be reassessed, however, because only a small, unpredictable fraction of the impactor ends up dissolved in seawater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Our results have obvious implications for estimating impactor size for a specific event, such as the Chicxulub impact. The size of the impactor that triggered the K-Pg extinction has been controversial owing to conflicting interpretations of geophysical and geochemical evidence (Morgan, 2008;Paquay et al, 2008). Collins et al (2020) showed that an impact angle of 45-60° is most consistent with geophysical observations of the Chicxulub crater.…”
Section: Implications For Crater Populations On Planetary Surfacesmentioning
confidence: 99%
“…Our results have obvious implications for estimating impactor size for a specific event, such as the Chicxulub impact. The size of the impactor that triggered the K-Pg extinction has been controversial owing to conflicting interpretations of geophysical and geochemical evidence (Morgan, 2008;Paquay et al, 2008). Collins et al (2020) showed that an impact angle of 45-60° is most consistent with geophysical observations of the Chicxulub crater.…”
Section: Implications For Crater Populations On Planetary Surfacesmentioning
confidence: 99%
“…The only two such excursions in the Cenozoic are Chicxulub (Figure 1b) and the late Eocene (~35 million years ago; Poag et al, 1994;Bottomley et al, 1997) dual impacts at Chesapeake Bay on the North American Atlantic coastal plain and Popigai in Siberia (Figure 1c; Robinson et al, 2009;Peucker-Ehrenbrink and Ravizza, 2012). Such Os isotope excursions would only be expected from chondritic impactors, but it is important to note that the scale of the impact is not necessarily reflected in the size of the Os excursion (Morgan, 2008). Other major climate events that have been proposed to be associated with impacts, such as the Paleocene-Eocene Ravizza, 2012).…”
Section: Marine Record Of Impactsmentioning
confidence: 99%